Gereformeerde mistiek en die neerslag daarvan in piëtistiese ego-tekste van manlike gelowiges in die Suid-Afrikaanse pionierslewe - Raath, Andries W. G. (HTS teologiese studies, 2012)
Reformed mysticism and the culmination thereof in pietistic ego-texts of male believers in the South African pioneer life on the frontier. The manifestation of Reformed mysticism in the pioneering communities of the South African interior was not limited to women-believers only. Although less frequent, Reformed mysticism contained in the pietistic ego-texts of male-believers also surfaced in early pioneering communities of South Africa. This essay considers the mystical ego-text of Francois Retief (1773–1838), the brother of Piet Retief who was massacred with other Voortrekkers by the Zulu king Dingaan in February 1838. Francois Retief’s ego-text reflects typical elements of Jesus-centred bridal mysticism. Although it does not contain the radical features of bridal mysticism prevalent among women-believers on the frontier, it reflects intense levels of spiritual consciousness associated with the energetic levels of faith among Reformed believers under dire circumstances on the frontier.